Optimasi Umur Pakai dan Efektivitas Boiler Akibat Korosi Menggunakan Algoritma Particle Swarm - Reza Setiawan; Vera Pangni Fahriani; Sugeng Riyadi (Jurnal Serambi Engineering, 2021)
One of the causes of boiler pipe breakage is corrosion. The prediction of the lifetime of the tube and superheater effectiveness on the boiler shall be calculated to determine and predict the failure time. The prediction of the lifetime of the tube is a prediction of the time of the failure of the superheater tube in the boiler so that the return can be performed.  The effectiveness of the superheater in the boiler is a comparison of the heat transfer rate of the overheated tubes  inside the boiler. The research method was research and development, a computational program using an optimization process.  The variables used in the study were steam input temperature, metal tube temperature, steam outlet temperature, natural gas input temperature, natural gas mass flow rate,  vapour mass flow rate, and natural gas outlet temperature. This study takes a case study of the superheater boiler from the company. The results of calculation of the life expectancy of the operating conditions  shall be 11 years when the boiler data sheet is used and 14 years  for using the actual boiler data. Superheater effectiveness in boilers with 56% is a data sheet on boilers and 56% of the actual data. Optimization of the particle swarm algorithm predicted a  29 year  lifespan. The effectiveness of the superheater in the boiler is 86%.